Factors involved in treatment decision making for women diagnosed with ductal carcinoma in situ: A qualitative study. (December 2021) - Hatton, Amy; Heriot, Natalie; Zalcberg, John; Ayton, Darshini; Evans, Jill; Roder, David; Chua, Boon H.; Hersch, Jolyn; Lippey, Jocelyn; Fox, Jane; Saunders, Christobel; Mann, G.Bruce; et al.
Abstract: Whilst some of the diversity in management of women with ductal carcinoma in situ (DCIS) may be explained by tumour characteristics, the role of patient preference and the factors underlying those preferences have been less frequently examined. We have used a descriptive qualitative study to explore treatment decisions for a group of Australian women diagnosed with DCIS through mammographic screening. Semi-structured telephone interviews were performed with 16 women diagnosed with DCIS between January 2012 and December 2018, recruited through the LifePool dataset (a subset of BreastScreen participants who have agreed to participate in research). Content analysis using deductive coding identified three themes: participants did not have a clear understanding of their diagnosis or prognosis; reported involvement in decision making about management varied; specific factors including the psychosexual impact of mastectomy and perceptions of radiotherapy, could act as barriers or facilitators to specific decisions about treatment. The treatment the women received was not simply determined by the characteristics of their disease. Interaction with the managing clinician was pivotal, however many other factors played a part in individual decisions. Recognising that decisions are not purely a function of disease characteristics is important for both women with DCIS and the clinicians who care for them. Highlights: Factors other than the characteristics of the DCIS were involved in decisions about management. There was a lack of understanding about diagnosis and prognosis. There was inconsistent involvement by women in decision making about management. Factors such as perception of mastectomy and radiotherapy could act as barriers or facilitators in decision making.